2020
DOI: 10.1002/aur.2300
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Cortical GABA and Glutamate in Young Adults With Autism Spectrum Disorder

Abstract: The balance of excitation and inhibition in neural circuits is hypothesized to be increased in autism spectrum disorder, possibly mediated by altered signaling of the inhibitory neurotransmitter γaminobutyric acid (GABA), yet empirical evidence in humans is inconsistent. We used edited magnetic resonance spectroscopy (MRS) to quantify signals associated with both GABA and the excitatory neurotransmitter glutamate in multiple regions of the sensory and sensorimotor cortex, including primary visual, auditory, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 146 publications
(187 reference statements)
1
37
2
Order By: Relevance
“…Our study included 28 young adult participants on the autism spectrum (18 males, 10 females), and 35 NT comparison participants (21 males, 14 females). Data from these participants with ASD [58][59][60] and NTs 12,[58][59][60][61] were included in our recently published work. All participants were assessed by clinicians with extensive experience with ASD, under the supervision of a doctorallevel clinical psychologist who had achieved research reliability in the gold standard tools used to diagnose ASD.…”
Section: Methodsmentioning
confidence: 99%
“…Our study included 28 young adult participants on the autism spectrum (18 males, 10 females), and 35 NT comparison participants (21 males, 14 females). Data from these participants with ASD [58][59][60] and NTs 12,[58][59][60][61] were included in our recently published work. All participants were assessed by clinicians with extensive experience with ASD, under the supervision of a doctorallevel clinical psychologist who had achieved research reliability in the gold standard tools used to diagnose ASD.…”
Section: Methodsmentioning
confidence: 99%
“…The definition of standard reference GSH values within the different brain areas reported could lead to a better interpretation of the altered GSH levels recorded in subjects with neurological disorders, with insight into the possible role of GSH as a biomarker and therapeutic target. Referring to the reliability previously discussed and the sensibility of MEGA-PRESS, the most reliable GSH detected values were those of studies that used this technique in brain area analysis through a comparison between groups and in clinical applications [ 3 , 10 , 67 , 74 , 77 , 83 , 95 , 96 , 97 , 98 , 99 , 100 ].…”
Section: Brain Areas Gsh Concentrationmentioning
confidence: 99%
“…However, almost all of these studies were carried out with indirect measurements of GSH in the blood or post-mortem [ 128 ]. More recent studies with 3 T MRS through the in vivo evaluation of GHS levels found no significant difference in GSH levels between patients with ASD and the controls (Durieux et al mean concentration 2.5 mM in the dorsomedial prefrontal cortex and 2.8 mM in the basal ganglia of both ASD patients and HC) [ 99 , 128 ].…”
Section: Clinical Applications Of Gsh Imagingmentioning
confidence: 99%
“…The possibility that there could be a neural basis for the lack of an undershoot in ASD may have significant implications for understanding the neural circuits that are disrupted and may provide specificity for long-standing speculation that disrupted inhibition contributes to ASD. Despite the evidence for disrupted inhibition, we note that this same cohort of ASD and NT subjects did not have any differences in GABA concentration in some of the same brain regions that exhibited differences in undershoot magnitude (e.g., visual, auditory, and somatomotor ROIs) as measured with MRS (Kolodny et al, 2020b). Thus, the fMRI undershoot may reflect an inhibitory process that is not captured by MRS measurements of GABA.…”
Section: Discussionmentioning
confidence: 65%
“…Other data from these same (or subsets of these) subjects have been described elsewhere (Millin et al, 2018 ; Murray et al, 2018 ; Schallmo et al, 2018 , 2019 ; Kolodny et al, 2020a , b ). Most relevant is the Millin et al’s ( 2018 ) study.…”
Section: Methodsmentioning
confidence: 98%